TOURISM AS A POLITICAL INTERSTATE DIALOGUE - Anna Sergeevna Matveevskaya (Science and Innovation Center Publishing House, 2018)
International tourism in the 21st century is an important factor in the world politics’ development. The growth of tourist flows and the worldwide scale of travels define tourism as part of the overall internationalization process of socio-economic relations. The tourism industry is developing quite stably and efficiently in many countries. National policies should be focused on obtaining the maximum benefit from international cooperation. The importance of international tourism in political discourse emphasizes the creation of international legal acts regulating the tourism industry, as well as different levels of tourist organizations. International tourism in world politics has a special advantage in resolving disagreements between states. The role of tourism in shaping the image and prestige of the country is noted. Russia’s participation in international tourism projects is a source of cultural, social and economic development. Interstate tours contribute to the development of cultural tourism into the sustainable development policies of countries and regions. A positive trend is the consent of the foreign partners on the inclusion of Russian tourist destinations in the perspective of cultural routes.